Synthesis and in vitro evaluation of neutral aryloximes as reactivators of Electrophorus eel acetylcholinesterase inhibited by NEMP, a VX surrogate. (25th August 2019) - Cavalcante, Samir F. de A.; Kitagawa, Daniel A.S.; Rodrigues, Rafael B.; Bernardo, Leandro B.; da Silva, Thiago N.; dos Santos, Wellington V.; Correa, Ana Beatriz de A.; de Almeida, Joyce S.F.D.; França, Tanos C.C.; Kuča, Kamil; Simas, Alessandro B.C.
Abstract: Casualties caused by nerve agents, potent acetylcholinesterase inhibitors, have attracted attention from media recently. Poisoning with these chemicals may be fatal if not correctly addressed. Therefore, research on novel antidotes is clearly warranted. Pyridinium oximes are the only clinically available compounds, but poor penetration into the blood-brain barrier hampers efficient enzyme reactivation at the central nervous system. In searching for structural factors that may be explored in SAR studies, we synthesized and evaluated neutral aryloximes as reactivators for acetylcholinesterase inhibited by NEMP, a VX surrogate. Although few tested compounds reached comparable reactivation results with clinical standards, they may be considered as leads for further optimization. Highlights: A practical method for synthesis of neutral aryloximes is presented. A VX surrogate was used as inhibitor for Electrophorus eel Acetylcholinesterase. Neutral aryloximes retrieved promising predicted properties for use as reactivators. Seven compounds were identified as potential leads for further optimization.